The megalopa stage of Portunus spinimanus Latreille, 1819 and Portunus gibbesii (Stimpson, 1859) (Decapoda, Brachyura, Portunidae) from the southeastern Atlantic coast of the United States - Negreiros-Fransozo, Maria Lucia [UNESP]; Meyers, Nadia; Fransozo, Vívian [UNESP]; Thorton-De Victor, Susan (My University, 2007)
The identification of megalopae from plankton samples is difficult, because this larval stage is the least well known among crab larvae, unknown in some species and poorly described in others. Wild megalopa specimens of some swimming crabs (family Portunidae Rafinesque, 1815) were captured alive from neuston samples obtained during summer surveys near the coast of Charleston, South Carolina (U.S.A). For identification purposes, larvae were reared to the 8th juvenile instar. After reaching the 5th juvenile instar, the juvenile crabs exhibited morphological features suitable for identification to the species level. The specimens belonged to two species of Portunidae, Portunus spinimanus Latreille, 1819 and P. gibbesii (Stimpson, 1859). Their megalopae were described in detail and compared to other portunid megalopae known from the southeastern Atlantic coast of the U.S.A. Species-specific characters of portunid megalopae are the number of carpal spines on the chelipeds, the relative size of the sternal spines (7th sternite), the number of antennal flagellum segments, and the setation of mouthparts. Copyright © 2007 Magnolia Press.
Keywords: Brachyura; Decapoda; Megalopa; Neusten; Portunus; U.S. Southern Atlantic coast; Decapoda (Crustacea); Portunidae; Portunus gibbesii; Portunus spinimanus